New Managers : mastering the big 3 principles of effective management-leadership, communication, and team building - Falcone, Paul (Nashville : HarperCollins Leadership, 2022)
"An accessible and practical playbook by leading HR expert Paul Falcone to cultivate your most vital resource: having the right people working hard for you"--
Includes index.
Keywords: Personnel management; Communication in management; Business communication; Supervision of employees; Leadership